Introgression of the Self-Pruning Gene into Dwarf Tomatoes to Obtain Salad-Type Determinate Growth Lines - Lucas Medeiros Pereira; Gabriel Mascarenhas Maciel; Ana Carolina Silva Siquieroli; José Magno Queiroz Luz; Ana Luisa Alves Ribeiro; Camila Soares de Oliveira; Frederico Garcia Pinto; Brena Rodrigues Mota Ikehara (Plants, 2024)
The use of dwarf plants in tomato breeding has provided several advantages. However, there are no identified dwarf plants (dd) containing the self-pruning habit (spsp). The aim of this work was to obtain future generations, characterize the germplasm, and select potential dwarf plants with a determinate growth habit to obtain Salad-type lines. The work was started by carrying out hybridization, followed by the first, second, and third backcrosses. Once F2BC3 seeds became available, the introgression of the self-pruning gene (spsp) into dwarf plants (dd) began. Three strains of normal architecture and a determinate growth habit were hybridized with two strains of dwarf size and an indeterminate growth habit, thus yielding four hybrids. Additionally, donor genotype UFU MC TOM1, the commercial cultivar Santa Clara, and the wild accession Solanum pennellii were used in the experiment. Agronomic traits, fruit quality, metabolomics, and acylsugars content were evaluated, and dwarf plants with a determinate growth habit were selected. Hybrid 3 exhibited the highest yields. Visual differences between determinate and indeterminate dwarf plant seedlings were observed. It is suggested to carry out five self-pollinations of the best dwarf plant determined and subsequent hybridization with homozygous lines of normal plant architecture and determinate growth habit to obtain hybrids.